THE ROLE OF VILLAGE GOVERNMENT IN THE DEVELOPMENT OF TOURISM OBJECTS IN CEMAGI VILLAGE, MEMBWI DISTRICT, BADUNG REGENCY - NI PUTU DIAN PRATIWI UDAYANI; NYOMAN DIAH UTARI DEWI (Universitas Mahasaraswati K. Mataram, 2024)
This research was carried out with the aim of understanding the role of the village government in developing the tourism sector in Cemagi Village, as well as identifying what factors played a role in the Badung Regency Government. This research uses a qualitative approach in its implementation and uses a purposive sampling technique. The results of this research show that the Government plays a role as an entrepreneur and manager of these tourist attractions and through planning and monitoring their development.